2022
DOI: 10.1186/s13287-022-03125-2
|View full text |Cite
|
Sign up to set email alerts
|

Aucubin promotes bone-fracture healing via the dual effects of anti-oxidative damage and enhancing osteoblastogenesis of hBM-MSCs

Abstract: Background Aucubin (AU), an iridoid glucoside isolated from many traditional herbal medicines, has anti-osteoporosis and anti-apoptosis bioactivities. However, the effect of AU on the treatment of bone-fracture remains unknown. In the present study, the aims were to investigate the roles and mechanisms of AU not only on osteoblastogenesis of human bone marrow-derived mesenchymal stromal cells (hBM-MSCs) and anti-oxidative stress injury in vitro, but also on bone-fracture regeneration by a rat t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Dexamethasone potently enhances the osteogenic capability of BMP-2, induces selective proliferation of BMSCs, stimulates the expression of RUNX2, ALP, OPN, and OCN, and increases the mRNA expression level of ALP [31]. Noggin is inhibitory to the BMP2 induced by osteogenesis induction medium, which has been demonstrated in other articles [32,33]. As a result, Noggin not only inhibits the upregulated BMP2 induced by aloe polysaccharide treatment but also the BMP2 induced by osteogenesis induction medium.…”
Section: Discussionmentioning
confidence: 78%
“…Dexamethasone potently enhances the osteogenic capability of BMP-2, induces selective proliferation of BMSCs, stimulates the expression of RUNX2, ALP, OPN, and OCN, and increases the mRNA expression level of ALP [31]. Noggin is inhibitory to the BMP2 induced by osteogenesis induction medium, which has been demonstrated in other articles [32,33]. As a result, Noggin not only inhibits the upregulated BMP2 induced by aloe polysaccharide treatment but also the BMP2 induced by osteogenesis induction medium.…”
Section: Discussionmentioning
confidence: 78%
“…promotes bone-fracture healing partly via the canonical BMP2/Smads signaling pathway and suppresses oxidative stress indirectly through Nrf2/HO1 signaling pathway. [29].…”
Section: Herbal Materials In Accelerating the Bone Regenerationmentioning
confidence: 99%
“…Nevertheless, in high concentrations, ROS can induce strong cytotoxicity to damage cellular membranes, proteins, and DNA ( Zeng et al, 2022 ). As a result, excessive ROS will impair the normal cellular function, structure ( Yin et al, 2016 ), and harm the process of fracture healing ( Wang K. et al, 2022 ). Recent studies showed that the close relationship between EMF and ROS ( Li J. et al, 2018 ).…”
Section: The Mechanism Between Elf-pemfs Primary Cilia and Bone Fracturementioning
confidence: 99%